Documentary Films in Reducing The Incident of Stunting Based on Local Wisdom at The Pegang Baru Health Center - Evareny, Lisma; Khadijah, Siti; Sefrina, Yosi; Bachtar, Fitrina (POLTEKKES KEMENKES PADANG, 2024)
Stunting is one of the nutritional problems experienced by toddlers in the world today. In 2017 there were 22.2% or around 150.8 million toddlers in the world stunted. However, this figure has decreased compared to 2000, which was 32.6%. This quasi-experimental study employed a pre-test and post-test design using a control group. The study involved an intervention group of 42 respondents and control group of a further 42 respondents. The sample was selected using purposive sampling. The data were analyzed using a t-test. Respondents' knowledge was obtained on average before being given health promotion about stunting prevention at 21.00 and with a P Value of 0.000  0.05 which means that there is an influence of knowledge with the provision of health promotion about stunting prevention. The average attitude before being given health promotion regarding stunting prevention is 28.00 with a P value of 0.000 < 0.05 which means that there is an influence of knowledge by providing health promotion about stunting prevention. Health education through documentary film consisting of film about the growth and development of toddlers and stunting can increase mothers' knowledge and attitude about monitoring the growth and development of toddlers and is expected to prevent stunting.